Beliefs in conspiracy theories and the need for cognitive closure - LEMAN, Patrick J.; Cinnirella, Marco (Frontiers in Psychology, 2013)
An important component of conspiracy theories is how they influence, and are influenced by, the evaluation of potential evidence. Some individuals may be more open minded regarding certain explanations for events whereas others may seek closure and thus cut off a conspiracy explanation. Two studies examined the relationship between the need for cognitive closure (NFCC), levels of belief in real world conspiracy theories, and the attribution of conspiracy theories to explain events. A first, small (N=30) and preliminary study found no relationship between NFCC and beliefs in conspiracy theories, suggesting that both advocates and opponents of conspiracy explanations do not differ on this dimension. A second study (N=86) revealed that evidence for and against conspiracy theories had an influence on attributions of the likelihood of a conspiracy to explain a novel event. Specifically, after reading evidence individuals with high levels of belief in conspiracy theories tended to rate a conspiracy explanation as more likely whereas those with low levels of belief rated it as less likely. However, when the need for cognitive closure was experimentally lowered the effects of prior beliefs in conspiracy theories diminished.